The Role of Didactic Strategies in Optimizing the Training of Handball Players at the Wing Post – the Analysis of the Somatic Ind - Bernicu , Andrei Răzvan; Mihăilescu, Nicolae (Arena-Journal of Physical Activities, 2020)
Scope. Designing a didactic strategy means predictability, experience and adaptation of methods and means to the structure of human material, which highlights and differentiates it from the algorithm : the strategy offers alternatives, the option of manifesting intelligent behavior, while the algorithm involves a mechanical state of an action sequence. Methodology. The experiment took place between December 2017 - June 2018, in the city of Suceava, with the 18 team of Suceava Sports High School specialized on the wing post. During this period, the team maintained its regular training program, the wings following our proposed program to analyze its effect on improving the tracking parameters. We estimate that the scientific approach to training, from the perspective of the physical, technical and psychological components of sports training, will increase the competitive yield. Results. After we aplly our program we see the changes: - at the body fat of the extreme players decreasing significantly from 15.72 ± 3.42% to 13.57 ± 2.52%; - the level of active mass of our subjects recorded a statistically significant increase from 42.73 ± 1.97% to 45.97 ± 2.16%; - the basal energy needs of our athletes suffer a significant increase, from 1697 ± 127.6 kcal to 1818 ± 124.1 kcal. Conclusion. The training program has show us good results, but any planning can not achieve perfection, requiring continuous improvements, gait adjustments and additions in line with the requirements of modern handball. The proposed program can be continuously implemented in the research team, by adapting to the conditions of the moment and the proposed objectives.